Spatial Distribution and Pollution Assessment of Metals in Sediments of the Babon River, Central Java, Indonesia - Haeruddin Haeruddin; Agoes Soegianto; Frida Purwanti; Arif Rahman; Carolyn Melissa Payus; Hefni Effendi (Scientifica)
Background. The Babon River is one of the drainage channels in Semarang, Indonesia, that is used for drinking water, irrigated agriculture of paddy fields and gardens, fish farming media, and the disposal of industrial wastewater. This study aimed to assess the spatial distribution of metals in the sediment of the Babon River through the utilization of different pollution indices. These indices included concentration factor (Cf), contamination factor (CF), enrichment factor (EF), geoaccumulation index (Igeo), sediment pollution index (SPI), threshold effect level (TEL), and probable effect level (PEL). Methods. Seven sampling locations were sampled for water and sediment in April, June, and September of 2021. The measurement of the metal was conducted using an atomic absorption spectrophotometer. Results. The findings of the study demonstrated that sediments with a predominant sand texture exhibited higher levels of Cd and Pb, while the sediments characterized by a predominant clay texture had a higher concentration of Cr. Upon analyzing the Cf, CF, EF, Igeo, and SPI data, it has been confirmed that the sediment in the Babon River has substantial levels of Cd, Cr, and Pb. According to the TEL and PEL values, it can be observed that the presence of Cd and Pb has detrimental effects on the biological health of the benthic biota. Conclusions. The aquatic biota and the benthic environment may be subject to adverse effects in the event where the concentration of metals in the sediment is higher than the natural concentration of metals.